Evaluation of the quality of dried distiller's grains with solubles for normal and high sugary corn genotypes during dry–grind ethanol production - Zabed, H.; Boyce, A.N.; Sahu, J.N.; Faruq, G. (Elsevier, 2017)
High sugary corn genotypes (HSGs; Zea mays L.) have shown the potential to produce higher amounts of ethanol consuming lower quantity of enzymes during dry-grind (DG) ethanol production compared with those of parent field corn lines (PFCs). Dried distiller's grains with solubles (DDGS) is an important co-product for a DG plant, where the market value of DDGS is affected by its quality, particularly the physicochemical composition. In the present work, DDGS samples were studied for both HSGs and PFCs in a conventional and a non-cooking DG ethanol method under two enzymatic conditions to evaluate DDGS composition of the corn genotypes. Irrespective of the enzymatic conditions, the average yield of DDGS among the corn genotypes ranged from 25.07% to 32.44% for the conventional and 26.97%–31.69% for the non-cooking method. Compared to the DDGS of HSGs, significantly higher amounts of starch were recorded in the DDGS of PFCs in both methods when enzyme load was the lowest. Protein content in DDGS samples did not differ significantly between the two enzyme loads and the DG methods individually, but the combined effects of genotypes and DG methods had significant effects on the protein content. All the biochemical components of corn kernels significantly correlated with the respective components in DDGS under all conditions. In conclusion, HSGs produced DDGS with higher amounts of protein and ash, but lower amount of starch than those of PFCs.